Cell membrane enveloped polymeric nanosponge for detoxification of chlorpyrifos poison: In vitro and in vivo studies. (August 2021) - Altaf, S; Muhammad, F; Aslam, B; Faisal, MN
Organophosphates are highly toxic compounds as they are involved in irreversible inhibition of acetylcholinesterase, causing various neurotoxic effects via acetylcholine accumulation throughout the nervous system. Traditional treatments for organophosphate poisoning are not effective enough to overcome all the toxic effects. There is a need for alternate treatment of life threatening poisoning of organophosphates. For this purpose a biomimetic nanosponge of poly (lactic- co -glycolic acid) is prepared, characterized and analysed as an antidote for organophosphate poisoning. In this nanosponge red blood cell membranes are used for coating poly lactic co-glycolic acid nanoparticles. In vitro studies are conducted to investigate the retention of acetylcholinesterase activity on the prepared nanosponge as well as to assess the scavenging ability of prepared nanosponge for model organophosphate, chlorpyrifos. In vivo studies are conducted to evaluate the detoxification potential of nanosponge in rabbit model, poisoned with chlorpyrifos. Hepatotoxicity and renal toxicity of nanosponge/chlorpyrifos complex is also studied in survived rabbits and the data is analysed statistically.